Analytical regularities of inversionless superradiance - Алиса Сергеевна Горбачева; Игорь Викторович Рыжов (Physics of Complex Systems, 2022)
The article reports the results of a theoretical study of superradiance of three-level optical systems with a doublet in the ground state (Λ-scheme) placed in a high-quality cavity. Hyperbolic chaos and unpredictable dynamic movements of the system appear on the surface of a multidimensional torus without dissipative losses in the conditions of superradiance without population inversion. The study resulted in the development of conservation laws to reduce the dimension of the phase space. An analytical result is obtained for the special case of a degenerate doublet.